Difference in the characteristics of the rust layers on carbon steel and their corrosion behavior in an acidic medium: Limiting factors for cleaner pickling. (20th January 2017) - Ding, Jiewei; Tang, Bing; Li, Mingyu; Feng, Xianfeng; Fu, Fenglian; Bin, Liying; Huang, Shaosong; Su, Wen; Li, Danni; Zheng, Lichun
Abstract: This work aims at revealing the key factors that limit the cleaner production level of a pickling process. By comparing the difference in their characteristics and the corrosion behaviors in an acidic medium, three kinds of sample, including the matrix steel (AS), the naturally-corroded carbon steel (NR) and the carbon steel treated under high temperature oxidation (OR), after immersed in the experimental solutions with or without hexamethylenetetramine (HA), were characterized with the methods, such as, electrochemical polarization, X-ray diffraction (XRD) and scanning electron microscopy (SEM). Results indicated, no matter which kind of rust layers, the adsorption of HA on their surface all accorded with the same adsorption isotherm. Although the rust layers did not change the adsorption pattern of HA directly, but their steric effect would influence the adsorption potential of HA; the forming process of rust layers (under different environmental conditions) heavily influenced their composition, structure, and the interface roughness between the rust layer and the metal matrix, and also influenced the corrosion behavior of samples in an acidic medium, which were the key factors that limited the cleaner production level of a pickling process. These results indicated that an object-oriented pickling strategy should be adopted for a practical pickling process. Highlights: Characteristics of the rust layers was heavily influenced by the forming process. The steric effect of rust layer influenced the adsorption potential of HA. Rougher surface led to a higher corrosion potential. Easier adsorption of inhibitor caused more effective protection to the metal matrix.